Clinical Practice Guidelines for Cerebrovascular Disease Treatment - Rubén Bembibre Taboada; Diosdania Alfonso Falcón; Julio Héctor Jova Dueñas; Tania Pérez Ramos (Medisur)
Clinical Practice Guidelines for Cerebrovascular Disease Treatment. Even when this term makes reference to the whole process affecting part of cerebral vessel system and cerebral tissue, this document focuses on the cerebrovascular or acute neurological event abruptly affecting the cerebral tissue and the neurological condition of the patient. This condition is usually cause by an abrupt vessel occlusion, of thrombotic or embolic origin, or by subarachnoid or intraventricular intraparenchymatous hemorrhage, of aneurism origin, related with hypertension or with a tumour or arteriovenous defects. The main concepts, classification and conduct are reviewed, stressing the cerebrovascular accident. It includes assessment guidelines focused on the most important aspects to be accomplished.